Library Automated Self-service Machine (LASM) - British Invention Show 2009 - Jantan, Azizi; Jaafar, Ahmad Faizar; Jaafar, Ahmad Nazri; Kosnan, Ja'amayah; Mohd Radwan, Rizana (Perpustakaan Tun Abdul Razak, 2009)
This self-service flexible package allows library user to manage their own transactions easily and efficiently. Deliver self-service user friendly, faster, and simple to use.